Severe carvedilol toxicity without overdose - caution in cirrhosis - Satish Maharaj; Karan Seegobin; Julio Perez-Downes; Belinda Bajric; Simone Chang; Pramod Reddy (BMC, 2017)
Abstract Background Carvedilol is used in the management of hypertension, ischemic heart disease, heart failure and most recently, portal hypertension. It has been associated with improved outcomes regarding variceal bleeding, hepatic decompensation and death when compared to propranolol and endoscopic band ligation. The main cause of portal hypertension is cirrhosis and therefore carvedilol is increasingly used in these patients. Due to its extensive hepatic metabolism, carvedilol is contraindicated in severe hepatic impairment. However, there are no dosage adjustments in the manufacturer's labelling for mild to moderate hepatic impairment. Case presentation We present a case of cardiogenic shock that occurred after carvedilol 25 mg orally was administered to a patient with cirrhosis. As there was no overdose, the diagnosis was based on clinical recognition of the toxidrome. The patient was successfully treated with glucagon 5 mg bolus followed by infusion. Conclusions Patients with cirrhosis represent a special at-risk group for beta blocker toxicity. The typical threshold for carvedilol toxicity in overdose is 50 mg but in patients with cirrhosis this is not applicable. Nurses and physicians need to recognize the toxidrome early. Hospitals where carvedilol is used in patients with cirrhosis should have glucagon in formulary at doses to treat toxicity (bolus and infusion). Finally, dose adjustment and slow uptitration of carvedilol in cirrhosis is recommended.